Globalisation and solidarity - Kronsbein, Esther (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
In einer ländlichen Region Ugandas (Busoga) versuchen die Menschen ihren durch den zunehmenden Einfluss der Globalisierung erschwerten Lebensbedingungen zu begegnen und sich Handlungsspielräume zu schaffen. Aus postkolonialer Perspektive untersucht die Autorin die Rolle solidarischen Wirtschaftens hierbei. Dessen Nutzen als Überlebensstrategie wird ebenso beleuchtet wie sein Potenzial, Alternativen zu konventionellen Ansätzen wirtschaftlicher Entwicklung zu denken. An die Stelle westlichen „Expertentums“ tritt gelebte Erfahrung aus dem globalen Süden. Die Autorin beschreibt den Einfluss der Globalisierung auf den Alltag der Bevölkerung sowie auf soziale Ungleichheiten und stellt ihren postkolonialen Forschungsansatz detailliert dar. In a rural region of Uganda (Busoga), people are trying to manage their everyday lives and gain agency despite the negative effects of globalisation on their living conditions. In this book, from a postcolonial perspective, the author examines the role of solidarity-based economic activities in that process. She illuminates both the usefulness of solidarity-based economic activities as a survival strategy and their potential to offer alternatives to conventional approaches to economic development. Western ‘expertise’ is replaced by lived experiences from the global South. The author describes the influence of globalisation on the everyday life of the population as well as on social inequalities and presents her postcolonial research approach in detail.
10.5771/9783748930228
Keywords: Hochschulschrift; Globalisierung; Systemtransformation; Agraraußenhandel; Wirkungsanalyse; Sozialer Wandel; Solidarität; Agrargenossenschaft; Alternative Ökonomie; Postkolonialismus; Uganda; Wirtschaftsentwicklung; Selbsthilfe; Bedeutung; Rolle; Entwicklungstheorie; postkolonial; Global South; Solidarische Ökonomie; Post-Development; global capitalism; solidarity economy; Postcolonial; Social and Solidarity Economy; critical development studies; alternative economic activities; Soziale Solidarische Ökonomie; world-systems analysis; Postcolonial theory; Post-Development theory; Busoga; capitalist development; Afrika; Entwicklungspolitik; Africa; globalisation; development studies; Entwicklungsstudien; Entwicklung; globalization; development; solidarity; development aid; Fairer Handel; development policy; Fair Trade